Equação de Estado para o Universo Primordial - Medeiros, Léo Gouvêa [UNESP] (2007)
The main purpose of this thesis is to explore the role of the nuclear interactions during the early universe. For that, we import to cosmology an equilibrium statistical mechanics formalism based for relativistic interacting systems. Using this formalism and a phenomenological approach of the nuclear interactions, we built cosmological equations of state including photons, leptons and interacting hadrons and apply them to the cosmological standard model. Supposing certain extrapolations, the proposed equations of state are able to produce a primordial acceleration (inflation) continually linked with the radiation era present during the nucleosynthesis. This inflationary period is effective enough to solve the flatness and horizon problems, and it still allows a natural explanation for why the universe is expanding. However, we must stress that all these results are obtained only for a matter-antimatter symmetric universe. The research made suggest that the nuclear interactions are important for the early universe evolution and it might be the responsible for the inflationary period. This thesis has also the purpose of establishing a formal procedure able to include interaction terms as sources of gravitation in cosmology. This procedure is based in the ensemble theory of statistical mechanics, and can in principle be applied whenever the cosmic fluid is in thermodynamical equilibrium